Examining Predictors of Change in Emotionally Focused Couples Therapy - Dalgleish, Tracy L. (Université d'Ottawa / University of Ottawa, 2013)
Emotionally Focused Couple Therapy (EFT; Johnson, 2004) is an empirically validated approach to couple therapy that uses attachment theory to understand the needs and emotions of romantic partners. In EFT, relationship distress is conceptualized as resulting from negative affect, emotional disconnection, and unmet attachment needs. Although EFT is recognized as one of the most researched and effective approaches to couple therapy, little research has examined theoretically related characteristics of couples to changes in marital satisfaction throughout EFT. The present doctoral thesis examined this area of literature. Thirty-two couples were provided approximately 21 sessions of EFT. The goal of the first study was to identify intake characteristics related to change in marital satisfaction over the course of EFT. Couples completed self-report measures of marital satisfaction, attachment security, relationship trust, and emotional control at pre- and post-therapy and after each therapy session. Individuals higher on self-report attachment anxiety and higher levels of emotional control had greater change in marital satisfaction over the course of EFT. The goal of the second study was to examine intake levels of attachment security and its relationship to the occurrence of the blamer-softening event, a key change event in EFT, and changes in marital satisfaction. Results indicated that the occurrence of a blamer-softening event significantly predicted positive changes in marital satisfaction. Results also suggested that the occurrence of a softening event significantly moderated the relationship between attachment avoidance at intake and change in marital satisfaction from pre- to post-therapy. For couples who completed a blamer-softening event, partners with lower levels of attachment avoidance were more likely to have positive changes in marital satisfaction. However, this relationship was not evident for attachment anxiety. Overall, results from this thesis suggest that attachment security is a key characteristic of couple partners for therapists to consider when implementing EFT. Therapists may benefit from assessing attachment security at the start of therapy to help inform them of the emotion regulating strategies used by couple partners. This information may help therapists to tailor specific interventions such that couples may begin to develop more secure attachment bonds.
Keywords: Emotionally Focused Couple Therapy; Attachment Theory; Hierarchical Linear Modeling; Predictors; Blamer-Softening; Couple Therapy